Unified Carrier Regulation and Management Technology for Multiple Baseband Systems in High Throughput Satellite Network - LI Yan; ZHAO Yiyun; WANG Yixuan (天地一体化信息网络)
With the continuous progress of satellite internet technology, the main business of the satellite communication operation industry is evolving from traditional transponder leasing and video transmission to data transmission such as broadband access, which has brought about changes in the network construction mode and network operation and maintenance architecture of satellite operators. In order to meet the differentiated needs of different types of business applications on the network, operators often need to deploy multiple heterogeneous baseband systems. However, due to the incompatibility of different baseband systems, the frequency resources can only be scheduled in a certain system. Which result in a lack of flexibility in satellite resource planning and allocation. This article analyzed the carrier regulation and maintenance needs and challenges brought about by the above background, and studied the unified carrier regulation scheme for multi baseband systems, aimed to achieve reasonable and flexible allocation of spectrum resources, thereby fully unleashing the value of wireless network resources.